BH3 mimetics augment cytotoxic T cell killing of acute myeloid leukemia via mitochondrial apoptotic mechanism - Kapil Saxena; Shao-Hsi Hung; Esther Ryu; Shailbala Singh; Qi Zhang Tatarata; Zhihong Zeng; Zhe Wang; Marina Y. Konopleva; Cassian Yee (Cell Death Discovery)
Abstract Adoptive cell therapy (ACT) can address an unmet clinical need for patients with relapsed/refractory acute myeloid leukemia (AML), but its effect is often modest in the setting of high tumor burden. In this study, we postulated that strategies to lower the AML apoptotic threshold will augment T cell killing of AML cells. BH3 mimetics, such as venetoclax, are a clinically approved class of compounds that predispose cells to intrinsic apoptosis by inhibiting anti-apoptotic mitochondrial proteins. We explored the anti-leukemic efficacy of BH3 mimetics combined with WT1-specific CD8+ T cells on AML cell lines and primary samples from patients with a diverse array of disease characteristics to evaluate if lowering the cellular apoptotic threshold via inhibition of anti-apoptotic mitochondrial proteins can increase leukemic cell sensitivity to T cell therapy. We found that the combination approach of BH3 mimetic and CD8+ T cells led to significantly increased killing of established AML lines as well as of adverse-risk primary AML leukemic blast cells. In contrast to the hypothesis that enhanced killing would be due to combined activation of the intrinsic and extrinsic apoptotic pathways, our data suggests that CTL-mediated killing of AML cells was accomplished primarily through activation of the intrinsic/mitochondrial apoptotic pathway. This highly effective combinatorial activity due to convergence on the mitochondrial apoptotic pathway was conserved across multiple AML cell lines and primary samples, suggesting that mitochondrial priming may represent a novel mechanism of optimizing adoptive cell therapy for AML patients.